KINERJA JANGKA PANJANG INITIAL PUBLIC OFFERING DI INDONESIA UNTUK PERIODE TAHUN 2006-2009 - , HIMAWAN INDRA PUTRA SUNARYO, Agus Setiawan, Dr., M.Soc.Sc.,CMA. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Underperformance is often found during long term performance of Initial Public Offerings. Earlier studies suggest that underperformance happens in Indonesia. This research shows that the interpretation of performance depends on methods used. Iâm using data from 2006 until 2012, with samples of companies in Indonesia which launched their Initial Public Offering, then I classify those samples in categories based on their industrial sector. Method used are Wealth Relatives, Cumulative Abnormal Return, and Buy and Hold Abnormal Return. Using Wealth Relative, during the research period it is fund that outperformance happened in all of industrial sector except communication. While there are no significant underperformance nor outperformance found if Cumulative Abnormal Return and Buy and Hold Abnormal Return is used as interpretation method.